B105. Critical Care: Counterparts - Non-Pulmonary Critical Care and Multi-Organ Failure 2019
DOI: 10.1164/ajrccm-conference.2019.199.1_meetingabstracts.a4142
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Versus Central Testing of Hemoglobin During Large Volume Blood Transfusion

Abstract: Background: Point-of-care (POC) hemoglobin testing has the potential to revolutionize massive transfusion strategies. No prior studies have compared POC and central laboratory testing of hemoglobin in patients undergoing massive transfusions. Methods: We retrospectively compared the results of our point-of-care hemoglobin test (EPOC®) to our core laboratory complete blood count (CBC) hemoglobin test (Sysmex XE-5000™) in patients undergoing massive transfusion protocols (MTP) for hemorrhage. One hundred seventy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…9 In a retrospective study conducted by Herman et al with point of care device EPOC ® who compared the results with reference standard Sysmex XE-5000™, found that mean difference between the two was -0.268 (p=0.002). 10 In our study, mean difference with closed tube mode was -0.482 and it was -0.481 with open tube mode (p value <0.001). This showed that although the results were statistically significant, haemoglobin with point of care device was slightly higher than the reference standard.…”
Section: Discussionmentioning
confidence: 44%
“…9 In a retrospective study conducted by Herman et al with point of care device EPOC ® who compared the results with reference standard Sysmex XE-5000™, found that mean difference between the two was -0.268 (p=0.002). 10 In our study, mean difference with closed tube mode was -0.482 and it was -0.481 with open tube mode (p value <0.001). This showed that although the results were statistically significant, haemoglobin with point of care device was slightly higher than the reference standard.…”
Section: Discussionmentioning
confidence: 44%